Lateral Gradient Ambidextrous Optical Reflection in Self-Organized Left-Handed Chiral Nematic Cellulose Nanocrystals Films - Tao, Jiawei; Li, Jiaqi; Yu, Xiao; Wei, Lihong; Xu, Yan (Frontiers in Bioengineering and Biotechnology, 2021)
Artificial photonic materials displaying ordered reflected color patterns are desirable in the field of photonic technologies, however, it is challenging to realize. Here we present that self-assembly of cellulose nanocrystals (CNC) in a tilted cuvette leads to the formation of rainbow color CNC films. We show that the self-organized CNC films enable simultaneous reflection of left-handed circularly polarized (LCP) and right-handed circularly polarized (RCP) light with lateral gradient transmittance ratio (LCP/RCP: 8.7-0.9) and the maximum reflectance value up to ca. 72%. This unique ambidextrous optical reflection arises from left-handed chiral photonic architectures with lateral gradient photonic bandgaps and nematic-like defects at the film-substrate interface and between left-handed photonic bandgap layers acting as a half-wavelength retarder. We demonstrate that the tilted angle self-assembly method provides a feasible step towards color patterning of CNC-based photonic films capable of ambidextrous optical reflection.